Determinants of Consumer Willingness to Pay for Organic Mustard: Evidence from a Consumer Survey in Surabaya - Sholihah, Nadya Ash; Suprehatin; Muflikh, Yanti Nuraeni (HABITAT, 2024)
Currently, the Indonesian market for organic products is concentrated mainly in big cities such as Jakarta and Surabaya. This is a response to the rising interest of urban consumers in organic products including fresh vegetables. This study aims to examine consumers' willingness to pay (WTP) for organic mustard greens and relevant factors affecting consumers' WTP. The study used primary data from a 150-modern market consumer survey conducted in Surabaya during Mei-June 2023. The data were analyzed using a discrete choice experiment and logit regression model. The results showed that consumers were willing to pay a premium price ranging up to  Rp2393.2, Rp3517 and Rp5622.6 per bundle of better-quality of organic mustard greens based on fresh smooth green leaves, branded organic, and lebelled organic attributes, respectively. The results also showed that factors such as age, level of education, and family income significantly influence consumer’s WTP. The findings provide useful information to both policymakers to assist in designing policies for the promotion of organic vegetable production and marketing and organic vegetable business to formulate marketing strategies.